Spain : Financial Sector Assessment Program-Technical Note-Bank Resolution and Crisis Management Frameworks. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses the findings and recommendations in the Financial Sector Assessment Program for Spain in the areas of bank resolution and crisis management frameworks. The institutional framework in Spain has been strengthened and is more appropriate for managing the resolution process. At the Banking Union level, the Single Supervisory Mechanism is responsible for supervising all significant entities. The Single Resolution Board is the resolution authority for such entities, as well as for cross-border groups. Although the framework for bank resolution is well designed, the system could be enhanced. Recovery planning for Spanish banks is progressing, but further progress is warranted.